Chile : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Chile has successfully resisted contagion from neighboring countries difficulties. Chile's inflation targeting framework has successfully anchored inflation expectations and increased the economy's resilience to external shocks while maintaining price stability. The floating exchange rate regime is an essential part of the macroeconomic policy framework and continues to serve Chile well. The interest in recapitalizing the central bank is welcomed. Executive Directors commend Chile for the transparency of monetary and fiscal policies. Chile faces the essential task of returning to sustained economic growth and relatively low unemployment.